Book Review: General International Law â Jus Cogens: A General Inventory - Handayani, Irawati (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2018)
Jus cogens has been discussed for years by international law scholars around the world. Though there is no common agreement on the meaning of jus cogens of so-called peremptory norms, the majority of scholars seems to tacitly express their agreement on the highest position of jus cogens in international law. This book as mentioned in the title of the book is not an introductory book, refer to a book that explain the preliminary development of jus cogens.